Policy measures to expand home visiting programs in the postpartum period - Phung, Binh (Frontiers in Global Women's Health, 2023)
The postpartum period is characterized by a myriad of changes—emotional, physical, and spiritual; whilst the psychosocial health of new parents is also at risk. More alarmingly, the majority of pregnancy-related deaths in the U.S. occur during this critical period. The higher maternal mortality rate is further stratified by dramatic racial and ethnic variations: Black, brown, and American Indian/Alaska Native indigenous people have 3-4x higher rates of pregnancy-related deaths and severe morbidity than their White, non-Hispanic, and Asian/Pacific Islander counterparts. This policy brief explores how expanding evidence based home visiting programs (HVPs) and strengthening reimbursement policies that invest in such programs can be pivoted to optimize the scope of care in the postpartum period.